Developing and Validating a Novel Generic Patient-Reported Outcome Measure – Postoperative Recovery Scale for Adult (PRSA): A Prospective Observational Study - Liu Y; Yu R; Fu Y; Zuo Y; Qiu Y; Liu J (Patient Preference and Adherence)
Yijun Liu,1,2,* Rou Yu,3,4,* Yifan Fu,1,2 Yunxia Zuo,1,2 Yanhua Qiu,1,2 Jin Liu1,2 1Department of Anesthesiology, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2The Research Units of West China (2018RU012)-Chinese Academy of Medical Sciences, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 3Department of Anesthesiology, West China second University Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 4Key Laboratory of Birth Defects and Related Diseases of Women and Children, Ministry of Education (Sichuan University), Chengdu, Sichuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yanhua Qiu; Jin Liu, Department of Anesthesiology, West China Hospital, No.37 Guoxue Alley, Wuhou District, Chengdu City, Sichuan Province, People’s Republic of China, Email 1781585803@qq.com; scujinliu@gmail.comBackground: Quality of postoperative recovery is an important perioperative patient-reported outcome. However, there are limitations in the development process and content of existing scales.Purpose: To develop and validate a universal patient-reported outcome measure, the postoperative recovery scale for adult (PRSA), to assess early and long-term postoperative recovery.Patients and Methods: The PRSA was developed through a new conceptual framework, systematic literature review, patient interview, and Delphi consultation. Then, the PRSA and the 15-item quality of recovery scale (QoR-15) were employed to evaluate the measurement properties of PRSA in 180 adult patients undergoing abdominal surgery.Results: A 10-item PRSA scale was developed through a systematic review of 1602 literature, interviews with 138 patients, and two rounds of Delphi consultation. The correlation coefficient between the PRSA and QoR-15 ranged from 0.780 to 0.904 (P < 0.001), and the PRSA indicated great validity in distinguishing patients with complications. The internal consistency and test–retest reliability of the PRSA were satisfactory. Besides, the time to complete the PRSA was 27.5s (95% CI: 24.5– 30.0 s) shorter than QoR-15, and more patients thought that completing the PRSA was easy compared to QoR-15 (65.7% vs 57.2%, P < 0.001).Conclusion: The PRSA scale is a universal patient-reported outcome measure that can be utilized for evaluating postoperative recovery. It shows great measurement properties in patients undergoing abdominal surgery.Keywords: postoperative recovery, patient-reported outcomes, scale, abdominal surgery, adults